Chitosan Concentration and Cross-linker Volume Effect on The Release Kinetic of Red Ginger Oleoresin Microcapsule in Simulated Intestinal Fluid (SIF) Medium - Jayanudin Jayanudin; Moh. Fahrurrozi; Sang Kompiang Wirawan; Rochmadi Rochmadi (Eksergi, 2019)
Red ginger oleoresin contains components that can be used as antioxidants. Release kinetics studies are used to provide doses to achieve the desired drug concentration. The purpose of this study was to determine the release kinetics of red ginger oleoresin microcapsules based on changes in chitosan concentration and volume of cross-linker and determine the diffusion coefficient of red ginger oleoresin through microcapsule walls. Red ginger oleoresin microcapsules were prepared from a mixture of red ginger oleoresin in chitosan solution and stirred to form an emulsion. After that, it was added to corn oil and stirred again to form a second emulsion. Glutaraldehyde saturated toluene was added dropwise after finished added the 25% glutaraldehyde solution and remains stirred for 2 hours. Red ginger oleoresin microcapsules were separated and washed with petroleum ether and hexane, then dried in an oven. Microcapsules inserted in the release medium (simulated intestinal fluid) without enzymes, and then the samples were analyzed using a UV-vis spectrophotometer to determine the absorbance. The release kinetics models used were zero order, first order, Higuchi, Korsmeyer-Peppas, and Hixon-Crowell. The highest correlation coefficient (R2) was obtained from the Korsmeyer-Peppas release kinetics model, R2 = 0.73-0.85 with the value of n = 0.39-0.41. Based on the n value, the release mechanism of red ginger oleoresin microcapsules was Fickian diffusion. The diffusion coefficients obtained were 2,807 x 10-13 - 3,675 x 10-13 cm2 /sec.